Oxidative valorisation of lignin into valuable phenolics: Effect of acidic and basic catalysts and reaction parameters. (October 2021) - Kumar, Avnish; Biswas, Bijoy; Kaur, Ramandeep; Krishna, Bhavya B.; Thallada, Bhaskar
Graphical abstract: Highlights: Oxidative depolymerization of rice straw lignin was investigated with MgO and ZSM-5. Maximum bio-oil yield (50 wt%) was obtained with ZSM-5 in N2 environment. GC–MS results showed maximum (38.5%) selectivity towards 2-methoxy-4-vinylphenol. 1 H NMR and FT-IR analysis of bio-oil revealed the breaking of lignin into monomers. The mechanism of breaking of lignin into monomers was discussed. Abstract: The aromatic nature of lignin makes it a good source for the production of numerous platform chemicals. The valorization of lignin into valuable compounds depends upon the type of bonds and functionality present in lignin. Here, we have studied the depolymerization of rice straw alkali lignin in N2 and O2 with acidic (ZSM-5), basic (MgO) catalyst and with their mixtures (1:1, 3:7 and 7:3). The effect of hydrogen peroxide on lignin depolymerization was also examined. Maximum yield of bio-oil (50 wt%) was obtained with pure ZSM-5 and 1 ml hydrogen peroxide in nitrogen atmosphere, while maximum conversion (60%) was observed in oxygen environment during the non-catalytic depolymerization of lignin. Bio-oil characterization through GC–MS showed maximum selectivity towards 2-methoxy-4-vinylphenol with 38.5 area% in the bio-oil of ZSM-5-N2 . The bio-oils have also been characterized using 1 H NMR, FT-IR and GC–MS.